The Application of Amino Acid Racemization Geochronology of Tubipora sp. in Marine Terraces of Manokwari Region, West Papua, Indonesia - Hidayat, Rahmadi; Saputra, Sukahar Eka Adi; Husein, Salahuddin (Universitas Gadjah Mada, 2024)
The active neotectonics of northern West Papuan coastlines allow the formation of emergent marine terraces associated with Quaternary sea-level high stands. These terraces contain fossils from the coral assemblage, which are useful for geochronological assessments and further estimating uplift rates. Here, we report the applicability of amino acid racemization (AAR) of Tubipora sp. to discriminate different ages associated with stages of sea-level high stand, constrained by previous uranium-thorium (U/Th) series dating. The results from amino acid dating of three samples reveal two distinct extents of racemization corresponding to terraces developed during Marine Isotope Stage (MIS) 5 sensu lato and 1. However, AAR analysis could not further discriminate interstadial MIS 5a and 5c as determined by published radiometric dating. This indicates the low resolving power of amino acid dating to distinguish sub-sequences beyond the interglacial period. Nevertheless, the cost-effective and rapid analysis of AAR dating of Tubipora sp. can be used as preliminary results related to marine terraces formed in different interglacial events.